Imaging Adipose Tissue Browning using Mitochondrial Complex-I Tracer [18F]BCPP-EF. (31st May 2022) - Goggi, Julian L.; Hartimath, Siddesh; Khanapur, Shivashankar; Ramasamy, Boominathan; Tang, Jun Rong; Cheng, Peter; Barron, Anna M.; Tsukada, Hideo; Robins, Edward G.
Abstract : Browning of white adipose tissue (WAT) into beige adipocytes has been proposed as a strategy to tackle the ongoing obesity epidemic. Thermogenic stimuli have been investigated with the aim of converting existing white adipose tissue, primarily used for energy storage, into beige adipocytes capable of dissipating energy; however, evaluation is complicated by the dearth of noninvasive methodologies to quantify de novo beige adipocytes in WAT. Imaging with [ 18 F]FDG is commonly used to measure brown adipose tissue (BAT) and beige adipocytes but the relationship between beige adipocytes, thermogenesis and [ 18 F]FDG uptake is unclear. [ 18 F]BCPP-EF, a tracer for mitochondrial complex-I (MC-I), acts as a marker of oxidative metabolism and may be useful for the detection of newly formed beige adipocytes. Mice received doses of the β 3-adrenergic agonist CL-316, 243 subchronically for 7 days to induce formation of beige adipocytes in inguinal white fat. PET imaging was performed longitudinally with both [ 18 F]FDG (a marker of glycolysis) and [ 18 F]BCPP-EF (an MC-I marker) to assess the effect of thermogenic stimulation on uptake in browning inguinal WAT and interscapular BAT. Treatment with CL-316, 243 led to significant increases in both [ 18 F]FDG and [ 18 F]BCPP-EF in inguinal WAT. The uptake of [ 18 F]BCPP-EF in inguinal WAT was significantly increased above control levels after 3 days of stimulation, whereas [ 18 F]FDG only showed a significant increase after 7 days. The uptake of [ 18 F]BCPP-EF in newly formed beige adipocytes was blocked by pretreatment with an adrenoceptor antagonist suggesting that beige adipocyte formation may be associated with the activation of MC-I. However, in BAT, uptake of [ 18 F]BCPP-EF was unaffected by β 3-adrenergic stimulation, potentially due to the high expression of MC-I. [ 18 F]BCPP-EF can detect newly formed beige adipocytes in WAT generated after subchronic treatment with the β 3-adrenergic agonist CL-316, 243 and displays both higher inguinal WAT uptake and earlier detection than [ 18 F]FDG. The MC-I tracer may be a useful tool in the evaluation of new therapeutic strategies targeting metabolic adipose tissues to tackle obesity and metabolic diseases.